Travelling Policies: - Diogo Gaspar Silva; Jorge Malheiros; Herculano Cachinho (Finisterra - Revista Portuguesa de Geografia)
Situating this Special Issue requires us to draw on relational connections and think through elsewhere. It fundamentally takes us back a couple of years to a series of convention centres, hotel conference rooms and a small restaurant in downtown Denver, Colorado – the host city of the 2023 Association of American Geographers (AAG) Annual Meeting. As a globally recognised forum of intellectual exchange, the AAG Annual Meeting brings together thousands of geographers and scholars from related disciplines to advance debates, generate cutting-edge ideas and rethink existing or build new theorisations and tactics for understanding the complexities of twenty-first-century spatial processes and their path-dependent trajectories.